2016
DOI: 10.3766/jaaa.14104
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hearing Loss in Patients with Cystic Fibrosis

Abstract: This study suggests that age and frequency of hospitalizations are key predictors of HL development. Increased awareness and regular screening for SNHL should be included in the routine care of CF patients, particularly those at the highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…This group further reported that 74% of these ears with SNHL had hearing loss in the frequency range ≥9.0 kHz (14). A retrospective study by Tarshish (12), reported on the risk factors and prevalence of SNHL in a large cohort of CF patients (mean age= 18 yr., SD = 10 yr.) who had received audiometric evaluations between 2007 and 2010. They found that 21% (37 of 178) had SNHL in at least one ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group further reported that 74% of these ears with SNHL had hearing loss in the frequency range ≥9.0 kHz (14). A retrospective study by Tarshish (12), reported on the risk factors and prevalence of SNHL in a large cohort of CF patients (mean age= 18 yr., SD = 10 yr.) who had received audiometric evaluations between 2007 and 2010. They found that 21% (37 of 178) had SNHL in at least one ear.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 21% (37 of 178) had SNHL in at least one ear. However, of these ears 94.1% had unilateral SNHL, and 77.8% had bilateral SNHL at their highest test frequencies (6.0–8.0 kHz) (12). When we age matched our study (re: mean age of 26 yr., SD ±10) to Tarshish’s cohort, patients with CF between 20 to 49 years old, we found a prevalence for SNHL of ~42% within the conventional frequency range, all those had SNHL in the 6.0–8.0 kHz range, reflecting the normal progression of ototoxic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although we tend to focus on the proposition that patient response is attributable to some exacerbation management approaches that are superior to others, it may be as important to recognize practices that offer little or no difference in treatment response while significantly reducing treatment burden, resource utilization, and/or potential for patient toxicity. [31] Without prospective protocol-based comparative studies of different treatment regimens using efficacy measures considered both valid and compelling to CF patients, families, and care-providers, it will be difficult to optimize exacerbation treatment paradigms.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 33 , 54 The total cumulative number of IV courses of aminoglycosides (>10) and the total cumulative aminoglycoside dose induce a higher risk of ototoxicity. 35 , 40 , 76 , 77 In addition to conductive, sensorineural and mixed hearing loss, substantially higher rates of multiple symptoms associated with audiological disorders (such as tinnitus, imbalance and dizziness) have been reported in cystic fibrosis children compared with healthy controls. 54 Based on these findings, we suggest that routine hearing screening may be considered during and after aminoglycoside exposure.…”
Section: Discussionmentioning
confidence: 99%